Tire wear particle microbiome-derived extracellular vesicles function as potent vectors amplifying antimicrobial resistance risk in soil ecosystems - Qin, Yi-Fei; Pang, Jin-You; Li, Yang; Liu, Fang-Yu; Shen, Luo-Qin; Li, Hong-Zhe; Huang, Qiansheng; Yang, Zhugen; Zhu, Dong (American Chemical Society (ACS), 2026)
Tire wear particles (TWPs), a ubiquitous and characteristic pollutant of the Anthropocene, are emerging as a critical environmental hotspot for pathogenic bacteria and antibiotic resistance genes (ARGs). Despite concentrating these threats, the nanoscale mechanisms driving ARG dissemination from TWPs remain elusive. Here, we identify bacterial extracellular vesicles (EVs) as a critical, yet overlooked, vector for resistance transfer within the TWP plastisphere. We found that the TWP microhabitat stimulated a significantly higher proportion of colonizing potential pathogens to release EVs (46.3%) compared to bulk soil and water combined (7.3%). Moreover, these TWP-derived EVs were selectively enriched with critical ARGs, notably those conferring multidrug and tetracycline resistance. Functionally, we confirmed that these ARG-loaded EVs could transfer resistance traits, significantly enhancing the survival of Pseudomonas aeruginosa PAO1 and Escherichia coli DH5α under antibiotic stress. Together, our findings demonstrate that TWPs induce colonized pathogens to release ARG-carrying EVs, which subsequently enhance the phenotypic antibiotic resistance of recipient pathogenic bacteria. This study reveals that TWP-derived EVs serve as a bridge between environmental and clinical resistomes, representing a new urbanization-driven pathway in the antimicrobial resistance crisis.
Keywords: Tire wear particles; Urbanization; Antimicrobialresistance; Pathogens; Extracellular vesicles; 41 Environmental Sciences; Infectious Diseases; Emerging Infectious Diseases; Antimicrobial Resistance; Biodefense; Infection; 4004 Chemical engineering; 4105 Pollution and contamination